STRATEGIES FOR ENSURING THE ECONOMIC SECURITY OF ENTERPRISES - BOIKO, Vitalii; LISKEVYCH, Sofiia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article is devoted to the study of the processes of ensuring the economic security of enterprises on the basis of a strategic approach. The concept of the economic security system of the enterprise is defined. The main problems preventing the provision of economic security of enterprises at the current stage of their development have been identified. The SWOT-analysis of the system for ensuring the economic security of the enterprise was carried out, which made it possible to determine its weaknesses and strengths, potential opportunities and threats. The concept of economic security strategy of the enterprise was formed, which should be understood as a set of priority conceptual approaches and mechanisms for ensuring it in the conditions of structural changes and systemic transformations, which form the prerequisites for building effective tools for the protection of its economic interests, increasing the efficiency of functioning and ensuring dynamic competitiveness on the market in the long period. Basic strategies for ensuring the economic security of the enterprise were proposed, including legal-force (aimed at the implementation of institutional-legal support and physical protection of the enterprise’s property), resource-functional (provides for the rational use of production-resource potential taking into account specialization and economic traditions), system-diversified (oriented to the implementation of mechanisms for adequate countermeasures against risks and threats), market-logistic (provides formation of resource reserves for ensuring the economic security of the enterprise by means of improving market relations and optimizing the logistics flows of the enterprise) and structurally-balanced (aimed at harmonizing the structural and functional components of the economic security of the enterprise with basic components of its sustainable development).